Effect of gamma linolenic acid pretreatment on diabetic neuropathy in rats - ., Nishikant; Singh, Janardhan; Sood, Sushma; ., Vijayshanker (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The present study was planned to evaluate the preventive effects of gamma linolenic acid (GLA) on STZ induced diabetic neuropathy Methods: Streptozotocin (STZ) induced diabetic neuropathy in rats was monitored by measuring blood sugar levels, body weight, motor nerve conduction velocity (MNCV) and nociception. Forty rats were divided into 4 groups of 10 each. Group 1: control (vehicle), Group 2: STZ (50 mg/kg, i.v., single injection), Group 3: Gamma linolenic acid (50 mg/ kg, p.o., daily + STZ), Group 4: STZ + Insulin (4 units/kg, s.c., bid). Similar protocol was used for other parameters also. Results: Gamma linolenic acid pretreatment failed to reduce blood sugar levels in diabetic rats but prevented deterioration of motor nerve conduction velocity as compared to STZ diabetic rats. A significant weight gain was observed in STZ diabetic rats pretreated with GLA as compared to rats received STZ alone. Hyperalgesia induced by STZ was antagonized by GLA Conclusions: Thus gamma linolenic acid prevents the development of neuropathic changes induced by STZ in rats.